Patent Trends Analysis as a Basis for Innovation Strategies - Nestor Brandão Neto; Lester Faria; Francisco Cristovão Lourenço de Melo (Foresight and STI Governance)
The analysis of patent trends reveals significant patterns that have the potential to drive technological advancements in specific domains, particularly by identifying emerging areas and research gaps. This study examines how the economic appropriation of research and development outcomes mirrors the dynamics of the innovation process and informs strategic planning, policy formulation, and innovation management. By conducting a detailed analysis of the economic appropriations made by public science and technology institutions within Brazil’s aerospace and defense sectors, we identify how these trends can inform proactive approaches to technological innovation. The institutions studied exhibit research and development and innovation dynamics that are finely tuned to the specific needs and trends of their technological fields, illustrating the increasing diversity of research and development interests and the complexity of the innovation ecosystems in which they operate. Ultimately, the success of innovation policies and strategies hinges on the ability to anticipate technological trends, strategically invest in high-potential areas, and efficiently transfer technologies to the productive sector. This ensures that institutions are well-positioned to respond quickly and effectively to technological changes and market opportunities, fostering sustainable development and technological progress.